(untitled) - Fransman, Martin (Brighton, Sussex, 1986)
This book is special studies in the change of technology, social, and economic development
Keywords: Technological innovations,Thay đổi công nghệ,Developing countries,Quốc gia đang phát triển; Economic policy,Chính sách kinh tế; Developing countries,Quốc gia đang phát triển